Production of organic flavor compounds by dominant lactic acid bacteria and yeasts from Obushera, a traditional sorghum malt fermented beverage - Mukisa, Ivan M.; Byaruhanga, Yusuf B.; Muyanja, Charles M. B. K.; Langsrud, Thor; Narvhus, Judith A. (Food science & nutrition, 2017)
Single and mixed starter cultures of lactic acid bacteria (LAB): Weissella confusa MNC20, Lactobacillus plantarum MNC21, Lactococcus lactis MNC24 and Lactobacillus fermentum MNC34 and yeasts: Issatchenkia orientalis MNC20Y and Saccharomyces cerevisiae MNC21Y were used to produce Obushera, a fermented sorghum beverage. Microbial counts, pH, sugars, organic acids, and volatile compounds in starter culture and spontaneous fermentations were monitored during 48 hrs. Maximum counts of LAB (8.4–9.4 log cfu g−1) and yeasts (7.5 ± 0.1 cfu g−1) starter cultures were attained in 6–48 hrs. Weissella confusa, Lc. lactis, and Lb. fermentum showed possible acid sensitivity while I. orientalis produced surface films. LAB starter cultures and their combinations with S. cerevisiae lowered pH from 5.83 to <4.5 (3.50–4.13) in a shorter time (12 hrs) than spontaneous fermentations (24 hrs). Lactococcus lactis and W. confusa metabolized glucose the fastest (p < .05) during the first 6 hrs. Lactobacillus fermentum, Lb. plantarum, and S. cerevisiae utilized glucose and maltose concurrently. Lactobacillus plantarum and S. cerevisiae additionally utilized fructose. S. cerevisiae metabolized sugars the fastest (p < .05) during the first 12–24 hrs. Lactobacillus plantarum and W. confusa produced the highest (p < .05) amounts of lactate (5.43 g kg−1) and diacetyl (9.5 mg kg−1), respectively. LAB also produced acetate, ethanol, acetaldehyde, acetone, and acetoin. Coculturing LAB with S. cerevisiae reduced (p < .05) lactate and diacetyl yield. Yeasts produced high amounts of acetaldehyde and methyl alcohols. Issatchenkia orientalis produced higher (p < .05) amounts of 2-methy- 1- propanol and 3-methyl- 1- butanol than S. cerevisiae. Combinations of LAB with S. cerevisiae produced a profile flavor compounds close to that of spontaneously fermented Obushera. These combinations can be adopted for controlled fermentation of Obushera and related fermented cereal products.
Keywords: Cereal fermentation; Lactic acid bacteria; Obushera; Sorghum; Starter cultures; Yeasts